Perceptions of aging across 26 cultures and their culture-level associates - Bratko, Denis; De Fruyt, Filip; Terracciano, Antonio; McCrae, Robert R.; De Bolle, Marleen; Costa, Paul T., Jr.; Aguilar-Vafaie, Maria E.; Ahn, Chang-kyu; Ahn, Hyun-nie; Alcalay, Lidia; Allik, Juri; Avdeyeva, Tatyana V.; et al. (2009)
Perceptions of aging were examined in 26 cultures. Samples within each culture filled in peer report version of NEO-PI-R specially designed for assessment of adolescent personality. Results are analyzed in order to estimate perceived age differences in personality.
Projekt MZOS
ENG